2019
DOI: 10.3889/oamjms.2019.854
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Surgical Residents at King Abdulaziz Medical City in Jeddah, Saudi Arabia

Abstract: BACKGROUND: Surgical residency program is considered one of the toughest residency programs, which affects quality of life of the residents during training years. To date, no study has evaluated quality of life among residents, especially surgical residents here in Saudi Arabia. AIM: The objective of this study is to evaluate quality of life among surgical residents. METHODS: The study is a cross-sectional study conducted during September 2018 in King Khalid Hospital at King Abdulaziz Medical City … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…18,19 Reasons for low HWI quality of working life could be explained because of lack of flexibility, long working hours and high job demands which could interface between home and work responsibility. 4 Another reason which is associated with our study, that almost two thirds of the sample were married and that might lower the subscale of Home-Work interface. A low work-life balance can negatively affect the lives of residents in and around their work environment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…18,19 Reasons for low HWI quality of working life could be explained because of lack of flexibility, long working hours and high job demands which could interface between home and work responsibility. 4 Another reason which is associated with our study, that almost two thirds of the sample were married and that might lower the subscale of Home-Work interface. A low work-life balance can negatively affect the lives of residents in and around their work environment.…”
Section: Discussionmentioning
confidence: 70%
“…[1][2][3] In another study, which was published in 2018, it was demonstrated that high levels of stress are strongly connected with depression, burnout and diminished quality of life among residents. [4][5][6][7][8] In a recent study that was conducted in 2019, the research has listed that overall well-being and health statues, increased probability of patients' exposure to possible adverse events, the continuousness of the patients' care post-call and the effect on residents' reliance on memory during night duty, as they preserved as indicators of the negative impact as a result of the 24-hour on-call system. 2 workplace performance.…”
Section: Introductionmentioning
confidence: 99%
“…If the problem is faced positively, the quality of life will be good. However, if the problem is faced negatively, the quality of life will also be bad [8], [9], [10]. This study indicated that people with diabetes mellitus before the intervention in the intervention group had a moderate quality of life (56%) and the control group had a poor quality of life by 55%.…”
Section: Discussionmentioning
confidence: 73%
“…The General Surgery Residency Training Program is known to be one of the most challenging programs, which has a huge impact on residents’ quality of life (QoL) during their training years [ 1 ]. In 2012, the World Health Organization defined quality of life (QoL) as the individual’s perception of their position in life in the context of culture, values, personal goals, expectations, standards, and concerns [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there is only one locally based study that has evaluated the quality of life among Saudi surgical field residents in 2019 in King Abdulaziz Medical City (Jeddah, Saudi Arabia), but there is no single study done specifically for Saudi general surgery residents in Saudi Arabia as a nationwide study. The aim of this study was to evaluate the quality of life among general surgery residents in Saudi Arabia and address the factors that are negatively affecting their quality of life [ 1 ].…”
Section: Introductionmentioning
confidence: 99%